Work purpose of the Third World Congress, held in Vienna from 3 to 9 September 1961 and the XI Argentine Congress of Obstetrics and Gynecology meeting in Buenos Aires from 20 to 28 October of the same year - Bedoya Hevia, Mariano (2015)
Appointed by the Society of Obstetrics and Gynecology in Lima, we concur to the aforementioned events, Drs. Mariano Bedoya (Secretary General of the Society) and Dr. Alberto Santos former president of the same.